Histamine intolerance (HIT) - Matysiak, Joanna (Journal of Medical Science, 2022)
Histamine intolerance (HIT) is food intolerance of non-immunological origin, and it results from an imbalance between the consumption of histamine with food and the organism ability to metabolize it. The patients with HIT were found to have a significantly reduced concentration of histamine-degrading enzymes, diamine oxidase (DAO) and histamine N-methyltransferase (HNMT). Factors which have been identified that are conducive to histamine intolerance are:  genetic factors, dysbacteriosis, chronic diseases – especially allergic and intestinal diseases, chronic infections, mastocytosis and some drug use. Clinical symptoms of histamine excess may affect various organs and systems - the most common are skin symptoms (pruritis, erythema) nausea, vomiting, abdominal pain, diarrhea, headaches and sometimes severe reactions with shortness of breath, arrhythmias, blood pressure drop, and even cardiac arrest.Diagnostic methods in HIT utilize determination of serum DAO, determination of histamine metabolites in urine, measurement of the histamine wheal in the 50th minute of the skin prick test (SPT), gastroscopy with intestinal biopsy, diagnostic and therapeutic test, oral histamine-challenge test and genetic tests.The mainstay of histamine intolerance treatment if a low-histamine diet. Patients should avoid products belonging to the three groups of food: containing large amounts of histamine, histamine liberators, and products inhibiting the activity of DAO. Additionally, supplements containing DAO and antihistamines can be used.
Keywords: histamine intolerance; diamine oxidase (DAO); pseudoallergy; low-histamine diet